Treatment effects on the compressive strength of Reactive Powder Concrete (RPC) at 7 days - Helmi, Masdar; Hall, Matthew R.; Rigby, Sean P. (2013)
Reactive powder concrete (RPC) is produced by controlling three main factors: additives to mix composition, pre-setting application of pressure, and post-setting heating. Densification of the mortar is achieved by the application of pressure (either unidirectional static load or omnidirectional air pressure load) in order to minimize the presence of macro defects in the form of entrapped air voids. Heat curing is applied after final setting with temperatures of at least 90 °C in order to accelerate the hydration and pozzolanic reactions. The purpose of this research was to characterize the relative effect of these three treatment approaches on the compressive strength of RPC at 7 days. The variables assessed in this study include heating rate, treatment curing types; and with/ without static pressure (8 MPa). The results show that a heating rate of 50 °C/hr preceded by pressure application for 2 days were the optimum conditions for statically-pressed RPC samples. Assuming variables of 8 MPa static pressure and 2-day heat curing at 240°C, compressive strength increased by: 6 % using static pressure only, 60 % using heat curing only, and 83 % using both static pressure and heat curing. Further work will investigate the micro structural and chemical composition within the interfacial transition zone and mineral product evolution during hydration in combination with high temperature/ pressure curing conditions.